Evaluation of immunological responses to recombinant Porin A protein (rPoA) from native strains of Neisseria meningitidis serogroups A and B using OMV as an adjuvant in BALB/c mice. (November 2017) - Afrough, Parviz; Bouzari, Saeid; Mousavi, Seyed Fazlollah; Asadi Karam, Mohammad Reza; Vaziri, Farzam; Fateh, Abolfazl; Behrouzi, Ava; Malekan, Mohammadali; Siadat, Seyed Davar
Abstract: Neisseria meningitidis is one of the main causes of sepsis and meningitis, which are two serious life-threatening diseases in both children and adolescents. Porin A ( porA ) from both serogroup A and B were cloned into the pET28a plasmid and expressed in E. coli BL21 (DE3). The protein was expressed in Escherichia coli BL21 (DE3) and confirmed by SDS-PAGE and Western blot analysis. BALB/c mice were subcutaneously injected three times with 25 μg of the recombinant PorA. Specific total IgG antibodies and isotypes were evaluated using ELISA assay. Opsonophagocytic assay (OPA) and Serum Bactericidal assay (SBA) were performed. Results showed that vaccinated mice exhibited higher levels of anti-Porin A (p < 0.05) with a predominant IgG1 response compared to the control group. Results from in vitro experiments indicated that N. meningitidis was opsonized with immunized-mice sera, and compared to non-immunized mice, immunized mice displayed significantly increased phagocytic uptake and effective intracellular killing. In this study, serogroup B N. meningitidis OMV of strain CSBPI G-245 and complete and incomplete Freund's adjuvant were used. Results demonstrated that Porin A could be a valuable target for the development of immunotherapeutic strategies against N. meningitidis . Highlights: This study designed new construct as a candidate vaccine against Neisseria meningitides . Our results were shown high significance of IgG, IgG1 and especially IgG2a. Finally, protective properties against infections confirmed by opsonophagocytosis assay and bactericidal assay. Our results showed Por (A + B) mixed with OMV as an adjuvant may be mentioned as the candidate vaccine against infections caused by Neisseria meningitidis.